Twelve Infallible Men: The Imams and the Making of Shi‘ism - Nicole Correri (International Institute of Islamic Thought, 2018)
Matthew Pierce’s first book, Twelve Infallible Men: The Imams and the Making of Shi‘ism, is a unique scholarly work about Ithnā Ash‘arī Shī‘ism and the development of communal identity. His main argument in this book is that the Shi‘a religious identity was shaped over time based on collective social memory and specific biographical depictions of spiritual leadership centered on the sacredness of the Prophet Muhammad and his family, the ahl al-bayt. While much scholarship on Shi‘ism is centered on the topics of succession, theological doctrines, or the specific rituals of ‘Ashura, Pierce focuses instead on how love and devotion towards the imams and the ahl al-bayt developed. His scholarly inquiry was piqued by his experience in the shrine city of Qum, Iran, where he was a resident and scholar of an inter-faith dialogue program from 2003-2006. There he observed firsthand the personal devotional lives of Twelver Shi‘as who cultivate personal connections and relationship with the imams through devotional ritual, seeking intercession, pilgrimages to shrines, mourning their suffering, and seeking their guidance. In Twelve Infallible Men this system of piety and devotion is traced to five early biographical figures. His primary source material was biographical works, in particular the five collective biographies of the imams written between 943-1150 CE: The Establishment of the Inheritance (Ithbāt al-waṣiya), attributed to al-Masʿūdī; Proofs of the Imamate (Dalāʾil al-imāma), attributed to Ibn Jarīr; The Book of Guidance (Kitāb al-irshād), by al-Mufīd; Informing Humanity (Iʿlām alwara), by al-Ṭabrīsī; and Virtues of the Descendants of Abū Ṭālib (Manāqib Āl Abī Ṭālib), by Ibn Shahrashub. Through his thematic and comparative analysis of these five sources Pierce traces the origin of communal remembrance and the Shi‘i system of piety utilizing the methodology of collective 57 memory studies. Throughout his text he notes broader religious rhetorical trends related to the geographic area and time period, such as the martyrdom narrative in early Christianity and the influence of miraculous stories to confirm saintly status, amongst others. In this way, Pierce situates the Shi‘i narrative within a wider milieu that speaks to sociological developments and broader religious experiences. The selected texts were all produced during the ‘Abbasid reign that was established by utilizing the legitimacy of ahl al-bayt as the source of proper Islamic leadership in their overthrow of the Umayyad regime. The ‘Abbasid era saw the development and emergence of Shi‘i scholarship and identity. Pierce could perhaps have given more historical context and analysis of anti-‘Alid sentiment (such as the institutionalized cursing of ‘Ali) during the Umayyad regime, as part of the development of sympathy and sorrow for the family of the Prophet. But one aspect of the Shi‘i narrative that Pierce analyzes in great depth throughout his work is the shared memory of suffering, primarily as demonstrated by the martyrdom of and the centrality of sorrow for the ahl al-bayt. In his analysis of narrative patterns and recurring symbols he is interested in revealing the needs of the believing community and what made these particular stories meaningful to them. The book is organized into five chapters. Crucial to this work is Pierce’s clarification of Sunni-Shi‘a disputes and the fluidity of how these identities developed and eventually solidified over time. He notes how this time period saw a variety of theological and jurisprudential debates, and the central aspects of what formalized into a Shi‘a identity, ritual, and concepts. The writings Pierce examines emerged during a period where Arabic literature was first taking shape and therefore demonstrate a process within the Islamic community at large of articulating specific narratives. The first chapter describes the canonization of the Twelve Infallibles. Pierce purposefully does not engage the polemics of the time, although these may have provided means to understand another facet of how the selected authors chose to craft their narrative. But he analyzes how the biographies of the imams became standardized over time—for example, how martyrdom was attributed to all of the imams after Mufīd’s writings and how Mufīd in particular set the standard for these narratives contributing to a coherent Shi‘a community with clear boundaries. In the second chapter Pierce explores the collective biographies’ central concern, namely the deaths of the Imams. Their tragic martyrdom becomes a theme in this genre of writing where suffering and grief comprise the proper Shi‘a response. Notably, Pierce also sheds light on the role of martyrdom in minority spiritual groups in the Near East. In this chapter Pierce also begins his gendered analysis, which is a highlight throughout the work, bringing in the tropes of the treacherous wife and the vulnerable bodies of the imams. These characterizations make the earlier narratives circulated, especially in Mufid’s writing, now unthinkable. Furthermore, emotional performances of grief and weeping emerge as demonstrations of piety, as well as being associated with political rebellion. Pierce explores how this emotional performance was in distinct contrast to the proto-Sunni traditionalists’ emphasis on controlling grief. The third chapter revolves around the themes of suffering and betrayal that permeate the biographies. Pierce investigates the arc of sacred history for Shi‘is as evidenced by their afflictions and the denial of their rights, which feature as central literary motifs in these primary sources, along with the symbols of suffering and outsiders. He discusses how the imams emerge as a distinctive type, as too do their betrayers. This chapter also features important events in Shi‘i history: the events of Ghadir and the martyrdom of Husayn in Karbala, a pivotal story in the Shi‘a community, but one that did not take central stage until later in these collective biographies. Love and devotion to the ahl al-bayt become salvific mechanisms that draw upon performances of mourning. Pierce also explores how religious ritual developed along with the narratives in the biographies. He continues his exploration of gender tropes where the female body is the site of mistrust and fear, specifically in the example of ‘A’isha. A central point of his book, elaborated in this chapter, is how the boundaries of the community were conceptually paired with the imams’ bodies. The fourth chapter is a systematic exploration of masculinity as revealed through the imams’ vulnerable bodies and the idealization of male performance. Pierce describes how masculine ideals as envisioned by the biographers comprise the concepts of virtue, manliness, and group loyalty. He explores how the narratives describe the physical appearance, miraculous achievements, and heroics of the imams. The importance of male heirs, courage, strength, and skill in weaponry are all gendered themes of the imams as characterized in the biographies. Pierce analyzes how these qualities render claims of their legitimacy as leaders, observing how their portrayals also exemplify refinement and self-control. With the exposition of miraculous knowledge and actions, Pierce describes how the imams find victory in the spiritual realms while having experienced loss in the physical world. This chapter also features an important discussion of Fatima in the collective biographies and a fascinating and unique description of her pious female embodied performance sanitized of all female bodily imperfections (most specifically, blood). This last part of chapter four leads into the final chapter, which explores birth narratives in the collective biographies. These narratives form a unique center around which Shi‘is could celebrate and demonstrate communal devotion; it also established a divine ordainment through the transmission of prophetic light to the imams. Pierce explains that a unique aspect of Shi‘i hagiography is how the biographers labor to establish the imams’ mothers’ purity and chastity. His analysis of the sanitized bodies and bodily functions of these mothers is of particular interest. Part of the unique function of the imam is the transmission of his leadership to his successor and is revealed in the way in which the imams occlude the mothers in nurturing and caring for their newborn. These birth narratives underscore the Shi‘i claims of divinely appointed and rightful spiritual leaders, giving evidence to the community of believers that the imams were clearly designated from birth. Pierce effectively explores the Shi‘i community of memory and how these biographers established communal boundaries. His exploration of these primary sources with attention to literary analysis and genre specific themes and symbols is distinctive, and brings a different perspective into Islamic studies. Pierce’s analysis of gender ideals is also elucidating and could be explored more deeply in future work. It is also worth noting that within the body of the text, he predominantly references women scholars in his and related fields. Pierce successfully establishes the case for the crafting and defining of socio-religious Shi‘i identity via biographical texts whose key themes include loyalty, mourning, and justice for rightful heirs who were pure, ideal, and miraculous men.